ANALYSIS OF Escherichia coli BACTERIA CONTENT IN FISH MEAT WITH VITEK 2 COMPACT - Pramita Wally (Asian Journal of Aquatic Sciences, 2022)
Transmission of Escherichia coli in food can occur through contact with infected workers, as well as tools and materials used during food processing. One way to determine the presence of E.coli in processed fish balls is to perform a bacteriological test. The purpose of this study was to detect the presence or absence of bacteria in fish balls so that it can be seen whether these meatballs are in the hygienic category and are suitable for consumption or not. This type of research is a laboratory experiment. This research was conducted at the Maluku Provincial Health Laboratory on 26-28 January 2022. The sample used in this study was fish balls taken by purposive sampling (taken according to research needs) for laboratory testing. Based on the results above, it shows that the E.coli bacteria found in the meatball samples during the phenotyping test with Vitek 2 compact both at a dilution of 10-1 to 10-3 were not identified because they had not passed the maximum limit. Based on the results obtained, it was found that the fish balls made by service participants in Mamala country were still in accordance with the criteria of the Indonesian National Standard (SNI) No.7388:2009 regarding the maximum limit of E.coli bacterial contamination in processed meat products made by the government for the protection of consumers regarding the quality of the product in circulation and declared to meet the requirements for the maximum threshold of microbial contamination in food if the value is 3/g for the status fit for consumption. The condition of the value of the test results of the fish balls sample under study is due to the fact that food makers or processors when processing fish balls still use the correct sanitation and hygiene principles and according to procedures